Equivalent‐circuit extraction for gallium nitride electron devices: Direct versus optimization‐empowered approaches. (3rd April 2022) - Jarndal, Anwar; Crupi, Giovanni; Alim, Mohammad Abdul; Vadalà, Valeria; Raffo, Antonio; Vannini, Giorgio
Abstract: This work focuses on the equivalent‐circuit modeling of microwave field‐effect transistors. Although the purely direct approach allows obtaining a good prediction accuracy in a straightforward way without the need of any optimization, optimization algorithms are often used to achieve an improved accuracy at the cost of a higher modeling complexity. The pros and cons of empowering the direct approach with optimization algorithms are discussed by focusing the analysis on a 1000‐μm periphery gallium nitride high‐electron‐mobility transistor on silicon carbide substrate. The comparison between the two different approaches is performed through an extensive analysis of the frequency‐dependent behavior of the small‐signal characteristics.